The Effectiveness of Brief Cognitive-Behavioral Therapy on Rumination and Experiential Avoidance in Patients with Irritable Bowel Syndrome - Boloorsaz Mashhadi, Hengameh; Agahheris, Mojgan (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: Among the physical problems, irritable bowel syndrome can affect the patient's psychological behavior, which makes it necessary to reduce this problem by using appropriate psychological treatments. Therefore, this study aimed to investigate the effect of brief cognitive-behavioral therapy on rumination and experiential avoidance in patients with irritable bowel syndrome. Method and Material: The research method is quasi-experimental with a pre-test, post-test, and control group with a two-month follow-up. The statistical population was all men with irritable bowel syndrome referred to Moheb Hospital in Tehran in 2024. The participants were 40 patients selected through convenience sampling and randomly assigned to experimental and control groups (20 people in each group). Brief cognitive-behavioral therapy was applied to the experimental group for 10 sessions (one 1-hour per week). The control group did not receive any intervention. In addition to the researcher-made demographic information checklist, the Ruminative Response Scale (RRS) (Nolen-Hoeksema & Morrow, 1991) and the Experiential Avoidance Questionnaire (Gamez et al., 2011) were used to collect data. Data were analyzed using repeated measures analysis of variance (ANOVA). Results: The mean rumination score and its dimensions in the experimental group improved significantly after the intervention compared to the control group (P<0.05). Brief cognitive-behavioral therapy was beneficial in reducing experiential avoidance and its dimensions in the experimental group compared to the control group (P<0.05), and the effects of this program on dependent variables sustained during the two-month follow-up period (P<0.05). Conclusion: The results showed that brief cognitive-behavioral therapy can improve rumination and experiential avoidance in patients with irritable bowel syndrome. We can conclude that by enhancing the techniques of this treatment, we can hope for further improvement in these patients' psychological and behavioral functions.